National policy for the prevention and control of cancer in the health care network of people with chronic diseases: a view based on Zygmunt Bauman (Research, Society and Development, 2020)
The article aims to discuss the National Policy for the Prevention and Control of Cancer in the Health Care Network of People with Chronic Diseases within the scope of the Unified Health System, addressing prevention and palliative care in the sociological perspective of Zygmunt Bauman. The relationships between health professionals and users at different levels, “glocalization”, social individualization, self-determination and the urgency of actions in the microsocial context were highlighted, taking as an example the motivational interview in Primary Health Care; in palliative care further strengthened by Resolution number 41 of October 31, 2018 and the Best at Home program, the strategic-organizational planning of these services was focused on the inclusion of family and community, evaluating sociological indicators of territoriality such as the regionalization of politics in addition to the primacy for the communicational process between team-family-sick. Anchoring in Baumanian sociology allows, in addition to theoretical exploration, the dissection of crucial points and propositions. We corroborate for Primary Care in screening, supported self-care actions and participatory culture in the Brazilian microsocial context to favor the resolution of macro-social problems.